DMD genotype correlations from the Duchenne Registry: Endogenous exon skipping is a factor in prolonged ambulation for individuals with a defined mutation subtype. Issue 9 (12th July 2018) - Wang, Richard T.; Barthelemy, Florian; Martin, Ann S.; Douine, Emilie D.; Eskin, Ascia; Lucas, Ann; Lavigne, Jenifer; Peay, Holly; Khanlou, Negar; Sweeney, Lee; Cantor, Rita M.; Miceli, M. Carrie; et al.
Abstract: Antisense oligonucleotide (AON)‐mediated exon skipping is an emerging therapeutic for individuals with Duchenne muscular dystrophy (DMD). Skipping of exons adjacent to common exon deletions in DMD using AONs can produce in‐frame transcripts and functional protein. Targeted skipping of DMD exons 8, 44, 45, 50, 51, 52, 53, and 55 is predicted to benefit 47% of affected individuals. We observed a correlation between mutation subgroups and age at loss of ambulation in the Duchenne Registry, a large database of phenotypic and genetic data for DMD ( N  = 765). Males amenable to exon 44 ( N  = 74) and exon 8 skipping ( N  = 18) showed prolonged ambulation compared to other exon skip groups and nonsense mutations ( P  = 0.035 and P  < 0.01, respectively). In particular, exon 45 deletions were associated with prolonged age at loss of ambulation relative to the rest of the exon 44 skip amenable cohort and other DMD mutations. Exon 3–7 deletions also showed prolonged ambulation relative to all other exon 8 skippable mutations. Cultured myotubes from DMD patients with deletions of exons 3–7 or exon 45 showed higher endogenous skipping than other mutations, providing a potential biological rationale for our observations. These results highlight the utility of aggregating phenotypic and genotypic data for rare pediatric diseases to reveal progression differences, identify potentially confounding factors, and probe molecular mechanisms that may affect disease severity. Abstract : Using patient data from the Duchenne Registry, DMD individuals were stratified into separate groups according to the predicted exon skip necessary to produce an in‐frame transcript. Delayed age at loss of ambulation was observed among DMD individuals amenable to skipping of exons 8 and 44, while exon 51 skippable individuals had earlier age of loss of ambulation.